DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN PUBLIC SERVICE IN MOGADISHU, SOMALIA - NOR, JAMAL NOR ALI; ABDULLAHI, MOHIADIN MOHAMUD (IJRDO - Journal of Social Science and Humanities Research, 2018)
The current globalization pressure which external pressure of trade and investment liberalization and globalization were relatively strong, funds from foreign countries are very important to support economic situation in emerging economy in Somalia, therefore, the competition for foreign fund in emerging market cannot be avoidable. Among FDI welcome developing counties are trying to change their infrastructure, increase incentive, and create good climate and policies for investment in order to attract FDI. Therefore, the Somalia government is working on a more attractive incentive package to encourage foreign investors by implementing new policies and incentive, without setting proper policies Somalia government could benefit the FDI. The general objective of this study was to examine the determinants of foreign direct investment in public service in Somalia. To find out the effects of Market-Seeking on foreign direct investment in Mogadishu, Somalia. To establish the effects of Resource-Seeking on foreign direct investment in Mogadishu, Somalia. To determine the effects of Efficiency-Seeking on foreign direct investment in Mogadishu, Somalia. A descriptive survey focuses on the research design and is concerned with addressing the particular characteristics of a specific population of subjects, either at a fixed point in time or at varying times for comparative purposes. The target population of this study was conducted employee of sea port, airport, public hospitals and road buildings in Mogadishu. The selected number of individuals were as a representative of the whole population under study. The formula which was used this study was Slog van’s formula which is states the sample size of employee in Mogadishu seaport, Airport, Public hospitals and Road building. Data collection methods used included questionnaire. The data collected was analyzed using the software called Statistical Package for the Social Sciences (SPSS) and results shown in terms of frequency distribution and percentages. A regression model will be applied to determine the relationship between market seeking, resource-seeking and efficiency-seeking as the independent variables and Foreign direct investment as the dependent variable. Researcher recommends Government should establish foreign investment policies that can guide government to give foreign companies the activities that home investors cannot or that need huge amount of capital that is difficult to home business people. Government should make training and integration of the human resource of the country. This is to enable citizenry acquire skill; education and exposure that would enable them contribute positively to economic growth wherever they find themselves employed either with the foreign or domestic firms and whichever sector they are in.